World pharmacists’ day 2024: celebrating a success in community engagement and health promotion / Farhana Fakhira Ismail, Aida Azlina Ali and Saliha Azlan - Ismail, Farhana Fakhira; Ali, Aida Azlina; Azlan, Saliha (Faculty of Pharmacy, 2024)
World Pharmacists’ Day 2024 was organised with enthusiasm through a collaborative event led by the Society of Pharmacy Students (SOPHYS) and the Faculty of Pharmacy Student Secretariat (SMF) in partnership with the Saujana Utama Residents’ Council (MPPSU). Held at Dewan MPKS, Saujana Utama, the program was officiated by Ybrs. Professor Ir. Ts. Dr. Mohamad Hafiz Mamat, Deputy Rector (Research and Innovation), Universiti Teknologi MARA (Selangor Branch). The event celebrated the invaluable contributions of pharmacists to improving public health while fostering community engagement.